Maintaining and Advancing Quality Cancer Care During a Global Pandemic. Issue 2 (March 2022) - Oyer, Randall Alan; Pierce, Lori; Lathan, Christopher; Sagar, Bhuvana
Abstract : Abstract: The care of patients with cancer occurs in a fast-moving, high-pressure, and high-stakes ecosystem. Early in 2020, that complex ecosystem was further complicated by the advent of the COVID-19 pandemic. We address actions taken by care providers and systems during the initial phases of the pandemic, and how those actions preserved lifesaving and life-sustaining cancer care despite severely constrained resources. We outline cancer care principles and guidelines that were developed, shared, and adopted by cancer care organizations across the country. Care delivery concerns that arose during the pandemic, including equipment and personnel shortages, moral distress for care providers, and exacerbation of health care inequities are addressed. Process and operations changes taken by payers to serve their clients are described. Lessons learned are highlighted, along with a call to action that we learn from the experience, broaden our cancer care delivery mission, and commit to structural changes that will permanently improve the capacity of cancer care teams.